Lime-Stabilized Black Cotton Soil and Brick Powder Mixture as Subbase Material - S. Srikanth Reddy; A. C. S. V. Prasad; N. Vamsi Krishna (Advances in Civil Engineering)
Various researchers, for the past few decades, had tried to stabilize black cotton soil using lime for improving its shrinkage and swelling characteristics. But these days, the cost of lime has increased resulting in increase in need for alternative and cost effective waste materials such as fly ash and rice husk ash. Brick powder, one among the alternative materials, is a fine powdered waste that contains higher proportions of silica and is found near brick kilns in rural areas. The objective of the study is to investigate the use of lime-stabilized black cotton soil and brick powder mixture as subbase material in flexible pavements. Black cotton soil procured from the local area, tested for suitability as subbase material, turned out to be unsuitable as it resulted in very less CBR value. Even lime stabilization of black cotton soil under study has not showed up the required CBR value specified for the subbase material of flexible pavement by MORTH. Hence the lime-stabilized black cotton soil is proportioned with brick powder to obtain optimum mixture that yields a better CBR value. The mixture of 20% brick powder and 80% lime-stabilized black cotton soil under study resulted in increase in the CBR value by about 135% in comparison with lime-stabilized black cotton soil. Thus it is promising to use the mixture of brick powder and lime-stabilized black cotton soil as subbase material in flexible pavements.